Trend fundamentals and exchange rate dynamics - Florian Huber; Daniel Kaufmann (ETH Zurich, KOF Swiss Economic Institute, 2015)
We estimate a multivariate unobserved components-stochastic volatility model to explain the dynamics of a panel of six exchange rates against the US Dollar. The empirical model is based on the assumption that both countries' monetary policy strategies may be well described by Taylor rules with a time-varying inflation target, a time-varying natural rate of unemployment, and interest rate smoothing. The estimates closely track major movements along with important time-series properties of the real and nominal exchange rates across all currencies considered. The model generally outperforms a simple benchmark model that does not account for changes in trend inflation and trend unemployment.
Keywords: F31; E52; F41; C5; E31; 330; exchange rate models; trend ination; natural rate of unemployment; Taylor rule; unobserved components-stochastic volatility model